Pemikiran Ekonomi Al-Ghazali - Faqih At Thariq Harahap; Adelia Khirani Lubis; Salbiah Salbiah; Miftahul Jannah; Widiya Wati; Fitri Hayati (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This journal examines the economic thought of Al-Ghazali, a prominent 11th century scholar and philosopher who made important contributions to the development of Islamic economics. The study revolves around Al-Ghazali's emphasis on the close relationship between economic activities and the moral and social values governed by Islamic law. In his view, the purpose of economics is not limited to the pursuit of material gain, but should also prioritize the welfare of society as a whole. The discussion covers Al-Ghazali's biography and educational background, economic ideas, including the concept of exchange, the development of markets, production activities, the barter system, the role of money, and the function of government in economics. Al-Ghazali underlined the importance of justice in the distribution of wealth as well as the responsibility of the state in managing economic activities in order to achieve a balance between profit and social responsibility. In addition, the article also discusses the influence of Al-Ghazali's thought on the growth of the Islamic economy and its relevance in facing today's economic challenges, such as social injustice and wealth distribution. The conclusion of this paper confirms that Al-Ghazali's economic principles are still significant as guidelines in building a just, ethical and sustainable economic system in modern times.